Миграция куликов рр. Calidris и Limicola на западе Украины - Струс, Ю.М. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2012)
Особливості міграції куликів-побережників вивчались на території орнітологічного заказника «Чолгинського», впродовж 1995-2012 рр. У вказаний період ми проводили абсолютні обліки куликів та відлов із вимірюванням основних біометричних параметрів, оцінкою жирності та линьки. За дослідний період виявлено 7 видів побережників. Серед них 4 види звичайні мігранти: Calidris minuta, C. ferruginea, C. alpina, C. temminckii; 2 види рідкісні пролітні: C. alba і Limocola falcinellus та 1 вид рідкісній залітний – C. canutus. Peculiarities of migration of waders from the genus Calidris and Limicola were studied in the Cholgyni Ornithological Reserve (Western Ukraine) over the period 1995-2012. During this period, we performed absolute counts and catching of waders. In captured birds biometrical parameters were measured according to standard methods. Also estimations of the fat reserves and moult stage were made. During the study period 7 species of sandpipers were revealed. Among them 4 species were common migrants: Calidris minuta, C. ferruginea, C. alpina, C. temminckii; 2 species were rare on passage: C. alba and Limocola falcinellus; one species was vagrant – C. canutus.